2018
DOI: 10.1016/j.energy.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the heat transfer performance of the recovery boiler superheaters using simulated annealing, surrogate modeling, and computational fluid dynamics

Abstract: The author independently initiated the research, conducted the research, and wrote the manuscript. Prof. Järvinen and Prof. Vuorinen provided valuable comments and guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 107 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The optimization of the a priori geometry using reliable numerical methods presents a significant problem in the design of such extremely large-scale systems. Maakala et al [11] endeavored to demonstrate a computational optimization framework and adjust the design of the superheater zone in order to improve heat transfer. A surrogate-based analysis and optimization (SBAO) approach is used to construct the CFD-optimization framework; this method includes a simulated annealing optimization algorithm, a local polynomial regression surrogate model, and a Reynolds-averaged Navier-Stokes (RANS) CFD model.…”
Section: International Journal Of Innovative Research In Computer Sci...mentioning
confidence: 99%
“…The optimization of the a priori geometry using reliable numerical methods presents a significant problem in the design of such extremely large-scale systems. Maakala et al [11] endeavored to demonstrate a computational optimization framework and adjust the design of the superheater zone in order to improve heat transfer. A surrogate-based analysis and optimization (SBAO) approach is used to construct the CFD-optimization framework; this method includes a simulated annealing optimization algorithm, a local polynomial regression surrogate model, and a Reynolds-averaged Navier-Stokes (RANS) CFD model.…”
Section: International Journal Of Innovative Research In Computer Sci...mentioning
confidence: 99%
“…However, a lack of information has been observed in literature regarding the "rules" for the design of boilers mixing channel. Nowadays, this issue can be overcome by the coupling of CFD and shape optimization algorithms, which represents a viable path toward a robust and fast design strategy [12,13,14,15,16,17]. In fact, optimization techniques allow to drastically reduce the time required by the trial and error procedure traditionally employed by the designer, who has to produce only a tentative initial geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The energy conversion performed through combustion in furnaces causes several pollutant emissions including carbon dioxide, carbon monoxide, and NOx. Past investigations have already shown that the computational fluid dynamics (CFD) simulation is a powerful tool to analyze various physical phenomena occurring in laboratory and large-scale furnaces/boilers [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%